Hybrid Approach in the Analysis of Bovine Milk Protein Hydrolysates as a Source of Peptides Containing Di- and Tripeptide Bitterness Indicators - Anna Iwaniak; Piotr Minkiewicz; Monika Hrynkiewicz; Justyna Bucholska; Małgorzata Darewicz (Polish Journal of Food and Nutrition Sciences)
The aim of this study was to employ a hybrid approach combined with a fragmentomic idea of research used to analyze bovine milk protein hydrolysates as a source of peptides with a potential bitter taste. Firstly, selected sequences of bovine milk proteins were in silico hydrolyzed using bromelain, ficin, papain, and proteinase K. Hydrolysis was simulated using the BIOPEP-UWM “Enzyme(s) action” tool. Potentially released peptides (called parent peptides) were analyzed for the presence of shorter peptide regions with bitter taste. Some of them were defined as peptide bitterness indicators. Then, in silico results were verified in the in vitro experiments with the use of a bovine milk protein concentrate (MPC) as a substrate. The verification included the MPC hydrolysis and identification of peptides in MPC hydrolysates using RP-HPLC and RP-HPLC-MS/MS, respectively. The hybrid analysis of bovine milk protein hydrolysates showed that all released peptides contained fragments with bitter taste and some of them were bitterness indicators, which could potentially determine the taste of a whole sequence. However, the results of in silico and in vitro hydrolysis were divergent. It was also reflected by the ranking of enzymes acting in silico and in vitro . Despite above discrepancies, our predictions concerning the release of peptides that may affect the bitter taste of a hydrolysate, contribute to bringing more insights into the taste of foods, especially if unwanted. However, before introducing a food product to the market, sensory studies are required to confirm (or not) its taste.